Cross-talk between IL-6 trans-signaling and AIM2 inflammasome/IL-1β axes bridge innate immunity and epithelial apoptosis to promote emphysema - Ruwanpura, Saleela M; McLeod, Louise; Dousha, Lovisa F; Seow, Huei J; West, Alison C; West, Alice J; Weng, Teresa; Alanazi, Mohammad; MacDonald, Martin; King, Paul T; Bardin, Philip G; Gabay, Cem; et al. (Proceedings of the National Academy of Sciences - PNAS, 2022)
Pulmonary emphysema is associated with dysregulated innate immune responses that promote chronic pulmonary inflammation and alveolar apoptosis, culminating in lung destruction. However, the molecular regulators of innate immunity that promote emphysema are ill-defined. Here, we investigated whether innate immune inflammasome complexes, comprising the adaptor ASC, Caspase-1 and specific pattern recognition receptors (PRRs), promote the pathogenesis of emphysema. In the lungs of emphysematous patients, as well as spontaneous and cigarette smoke (CS)-induced mouse models of emphysema, the expression (messenger RNA and protein) and activation of ASC, Caspase-1, and the inflammasome-associated PRR and DNA sensor AIM2 were up-regulated. AIM2 up-regulation in emphysema coincided with the biased production of the mature downstream inflammasome effector cytokine IL-1β but not IL-18. These observations were supported by the genetic blockade of ASC, AIM2, and the IL-1 receptor and therapy with AIM2 antagonistic suppressor oligonucleotides, which ameliorated emphysema in mice by preventing elevated alveolar cell apoptosis. The functional requirement for AIM2 in driving apoptosis in the lung epithelium was independent of its expression in hematopoietic-derived immune cells and the recruitment of infiltrating immune cells in the lung. Genetic and inhibitor-based blockade of AIM2 also protected CS-exposed mice from pulmonary alveolar cell apoptosis. Intriguingly, IL-6 trans-signaling via the soluble IL-6 receptor, facilitated by elevated levels of IL-6, acted upstream of the AIM2 inflammasome to augment AIM2 expression in emphysema. Collectively, we reveal cross-talk between the AIM2 inflammasome/IL-1β and IL-6 trans-signaling axes for potential exploitation as a therapeutic strategy for emphysema.